2010
DOI: 10.1186/1741-7007-8-1
|View full text |Cite
|
Sign up to set email alerts
|

THOC5/FMIP, an mRNA export TREX complex protein, is essential for hematopoietic primitive cell survival in vivo

Abstract: BackgroundThe transcription/export complex is evolutionarily conserved from yeast to man and is required for coupled transcription elongation and nuclear export of mRNAs. FMIP(Fms interacting protein) is a member of the THO (suppressors of the transcriptional defects of hpr1delta by overexpression) complex which is a subcomplex of the transcription/export complex. THO complex (THOC) components are not essential for bulk poly (A)+ RNA export in higher eukaryotes, but for the nuclear export of subset of mRNAs, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
158
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(171 citation statements)
references
References 35 publications
11
158
1
1
Order By: Relevance
“…We then examined the mRNA export function of THOC5 after etoposide treatment. We had previously generated a MEF cell line from THOC5 flox/ flox mice (Mancini et al 2010). Infection of THOC5/FMIP flox/flox MEF with Adenovirus carrying cre-recombinase and GFP genes (Ad-GFP-Cre) resulted in depletion of THOC5/ FMIP expression in these cells within 4 d after infection (Mancini et al 2010;Guria et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then examined the mRNA export function of THOC5 after etoposide treatment. We had previously generated a MEF cell line from THOC5 flox/ flox mice (Mancini et al 2010). Infection of THOC5/FMIP flox/flox MEF with Adenovirus carrying cre-recombinase and GFP genes (Ad-GFP-Cre) resulted in depletion of THOC5/ FMIP expression in these cells within 4 d after infection (Mancini et al 2010;Guria et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We had previously generated a MEF cell line from THOC5 flox/ flox mice (Mancini et al 2010). Infection of THOC5/FMIP flox/flox MEF with Adenovirus carrying cre-recombinase and GFP genes (Ad-GFP-Cre) resulted in depletion of THOC5/ FMIP expression in these cells within 4 d after infection (Mancini et al 2010;Guria et al 2011). Using this system, we previously identified 10 THOC5-dependent genes, such as Grb10 interacting GYF protein 2 (Gigyf2 or Tnrc15), protein kinase C binding protein 1 (Prkcbp1), twisted gastrulation homolog 1 (Twsg1), enhancer of yellow 2 homolog (Eny2), solute carrier family 11 (proton-coupled divalent metal ion transporters), member 2 (Slc11a2), DHHC domain containing 2 (Zdhhc2) zinc finger, inhibitor of DNA binding 2 (ID2), or gap junction membrane channel protein a 1 (Gja1) (Guria et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of recent evidence have suggested that metazoan THO has cell type-specific roles during development (Griaud et al, 2012;Kopytova et al, 2010;Mancini et al, 2010;Moon et al, 2011;Wang et al, 2009). In mice homozygous for a hyphomorphic Thoc1 allele, spermatogenesis was severely compromised due to defects in the expression of genes required for normal cell differentiation in the testis, while most other tissues appeared to be unaffected (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In mice homozygous for a hyphomorphic Thoc1 allele, spermatogenesis was severely compromised due to defects in the expression of genes required for normal cell differentiation in the testis, while most other tissues appeared to be unaffected (Wang et al, 2009). Using conditional knock-out mice, Mancini et al (2010) showed that THOC5 was an essential element in the maintenance of hematopoiesis, whereas it was less important in differentiated cell types such as hepatocytes and heart muscles. In addition, it has been shown that THOC1 was differentially expressed in human cancers; it was up-regulated in ovarian and lung tumors, while down-regulated in testis and skin tumors (Dominguez-Sanchez et al, 2011).…”
mentioning
confidence: 99%